A comparison of the structure and function of nematocysts in free-living and parasitic cnidarians (Myxozoa). Issue 10 (September 2020) - Americus, Benjamin; Lotan, Tamar; Bartholomew, Jerri L.; Atkinson, Stephen D.
Graphical abstract: Highlights: "Polar capsule" should be considered a nematocyst morphotype. "Polar capsules" and nematocysts have similar compositions and morphologies. Polar "filaments" are tubules with sealed ends and helical symmetry. Myxozoans lack a visible cnidocil, but detect physical and chemical stimuli as discharge triggers. A revised terminology is suggested for myxozoan capsules. Abstract: Myxozoans are obligate parasites that have complex life cycles requiring alternate vertebrate and invertebrate hosts, with transmission via microscopic waterborne spores. Unusually for parasites, they belong to the phylum Cnidaria, alongside thousands of free-living corals, sea anemones, jellyfish and hydrozoans. Their cnidarian affinity is affirmed by genetic relatedness and the presence of nematocysts, historically called "polar capsules" in myxozoan research. Free-living cnidarians utilise this cellular weaponry for defence, predation and adhesion, whereas myxozoans use it to anchor to their hosts as the first step in infection. Despite the 650 million years of divergence between free-living cnidarians and myxozoans, their nematocysts retain many shared morphological and molecular characters. Both are intra-cellular capsules with a single opening, and contain a coiled, evertable tubule. They are composed of unique nematocyst proteins, nematogalectin and minicollagen, and both likely contain an internal matrix of metal cations covalently bound to the anionic polymer poly-gamma glutamate. The rapid dissociation of this matrix and the resulting increase in internal osmotic potential is the driving force behind tubule elongation during discharge. In this review, we compare the structure and function of nematocysts in Myxozoa and free-living Cnidaria, incorporating recent molecular characterizations. We propose that terminology for homologous myxozoan structures be synonymized with those from other Cnidaria, hence, "polar capsule" as a taxon-specific nematocyst morphotype and "polar filament" as "tubule." Despite taxonomic divergence, genome reduction and an evolution to parasitism, myxozoans maintain nematocysts that are structurally and functionally homologous to those of their free-living cnidarian relatives.